Building blocks of sexuality - Jones, Christopher D. (HTS teologiese studies, 2021)
This article broadly discusses the building blocks of sexuality by referring to differences in brain development in the womb, specific genetic factors influencing sex-reversal phenotypes and how they give rise to different sexes and sexual orientations. Gender identity and expression are reviewed, and a practical road map is presented within which religious denominations can responsibly engage with human sexuality, especially same-sex lifestyles, within their spheres of influence. Our concerns, discussions and suggestions about this all-important facet of humanity are based on the intellectual richness and research of numerous scientists over an extended period of time in order to point out the most important building blocks of sexuality. Following a qualitative methodological approach, the article starts with the brain differences between men and women as determined in the womb. It is followed by a discussion of the ‘five sexes’ proposed by Anne Fausto-Sterling, the spectrum of human sexual characteristics and the birth of sexual orientations. The article then looks at bisexuality, gender identity and expression, and before our concluding remarks, at biology and how religion should deal with sexuality, more specifically homosexuality. However, we do not pay attention to animal sexual behaviour, paedophilia, bestiality, gender differences in behaviour and public response to research findings on sexual differentiations in the brain.Contribution: This article is part of a special collection that reflects on the evolutionary building blocks of our past, present and future. It is not only based on historical thought but also contemporary research. It fits well with the intersectional and interdisciplinary nature of this collection and journal.